The Potential of Basil Leaves (Ocimum Bacillicum L.) and Red Ginger (Zingiber Officinale) as Antidiabetic Agents: A Scoping Review - Rizky Wahyu Muthmainnah; Lilik Wijayanti; Ratih Dewi Yudhani (Indonesian Journal of Global Health Research, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to beta cell dysfunction in the pancreas, which prevents the effective production and/or utilization of insulin. Various factors contribute to the increase in the prevalence of diabetes in 2021, with 12.1% of cases occurring in urban areas compared to 8.3% in rural areas. Antidiabetic drugs such as metformin are widely used and have gastrointestinal side effects. Using natural alternatives can provide safe effects. Basil leaves (Ocimum basilicum) and red ginger (Zingiber officinale) are active ingredients that can be used as herbal medicines that are easily found anywhere and have long been known in various traditional medicines for diseases. Usually, people consume them as vegetables and herbal medicine. Basil leaves and red ginger contain natural compounds that are beneficial to health and can boost the immune system, including as antidiabetic agents. The purpose of this review is to present comprehensive information on basil leaves and red ginger that have antidiabetic activity, conducted using a scoping review starting with the PRISMA guidelines. The information for this article was obtained using Google Scholar, Science Direct, Semantic Scholar, and PubMed from 2015 to 2025 resulting in 1229 articles, The results of this review were obtained from 8 articles that were used and met the inclusion criteria. Basil leaves contain flavonoids, phenols, and tannins, which play a role in lowering blood glucose levels by increasing insulin sensitivity and antioxidant activity. Red ginger is rich in gingerol and shogaol, which can lower blood glucose levels and reduce oxidative stress in the body. Both plants have significant potential as natural antidiabetics in lowering blood glucose levels through various mechanisms.